FEATURES OF WHITE RATS STOMACH ANATOMICAL STRUCTURE - Hryn, V.H.; Kostylenko, Y.P.; Yachmin, A.I. (World of Medicine and Biology, 2019)
Judging by the literature, the human digestive tract and white rats have more similarities than differences. Investigation of specific features of the structure of the stomach of white rats is necessary for replenishment of modern morphological information about the possibility of studying the flow and modeling of certain pathological conditions. The work was aimed at a detailed study of the white rats stomach anatomical features. The study was performed on 80 white male rats. The material for the study was remote stomachs with the distal esophagus. After their removal fixed with 10% neutral formalin, photographing the outer and inner (mucosal) surfaces. In other cases, the content carried gastrointestinal tract of animals air through the esophagus, physiological saline, and self-hardening plastic (Latacryl-S), and then subjected to acid corrosion casts afford internal cavities of the stomach, small intestine and colon. After studying the anatomical features of the stomach of white rats can distinguish fundus of the stomach, body and pylorus. The presence of two different digestive processes (bacterial in the pre-stomach and fermentative in the glandular department), according to our data, is not sufficiently substantiated, given that there is no pronounced difference in the cavity between nonglandular (pre-stomach) and glandular (the stomach proper) departments. We proposed to replace the name of the pre-stomach with the «foundation department», and call the glandular zone «gastral department».